Physical activity in Sami and non-Sami populations in rural Northern Norway, the SAMINOR 2 Clinical Survey - Borch, Kristin Benjaminsen; Eliassen, Bent Martin; Melhus, Marita; Damsgård, Elin; Broderstad, Ann Ragnhild (BMC Public Health, 2021)
publishedVersion